2017
DOI: 10.1038/srep44232
|View full text |Cite
|
Sign up to set email alerts
|

Functional interactors of three genome-wide association study genes are differentially expressed in severe chronic obstructive pulmonary disease lung tissue

Abstract: In comparison to genome-wide association studies (GWAS), there has been poor replication of gene expression studies in chronic obstructive pulmonary disease (COPD). We performed microarray gene expression profiling on a large sample of resected lung tissues from subjects with severe COPD. Comparing 111 COPD cases and 40 control smokers, 204 genes were differentially expressed; none were at significant GWAS loci. The top differentially expressed gene was HMGB1, which interacts with AGER, a known COPD GWAS gene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(127 citation statements)
references
References 78 publications
7
120
0
Order By: Relevance
“…It is not known whether ACER2 with increased expression was associated with apoptosis of the emphysema in the present study. FAM13A, known as a COPD-related gene, was significantly upregulated in COPD with emphysema group ( P -value 0.00096), and this is consistent with many previous genetic studies 9,10…”
Section: Discussionsupporting
confidence: 90%
“…It is not known whether ACER2 with increased expression was associated with apoptosis of the emphysema in the present study. FAM13A, known as a COPD-related gene, was significantly upregulated in COPD with emphysema group ( P -value 0.00096), and this is consistent with many previous genetic studies 9,10…”
Section: Discussionsupporting
confidence: 90%
“…Then, the number of the 145 GWAS genes included in the DEGs was zscorenormalized and the p-value for the given z statistics was calculated; the p-value of 0.2 indicates that the number of differentially expressed GWAS genes is equal to what expected by chance. This observation is in accordance with the results obtained in [Morrow 2017], where the authors showed that COPD GWAS genes were not differentially expressed in lung tissue samples. The DEG matrix of 2097 rows (DEGs) and 327 columns (219 COPD cases + 108 control samples) was used as input to SWIM in order to build the COPD gene correlation network based on the Pearson correlation coefficient, where a threshold is set for the absolute value of the minimum correlation coefficient necessary to draw an edge (see Materials and Methods section).…”
Section: Copd Correlation Networksupporting
confidence: 92%
“…Instead, the gene KCND3 codes for potassium channel subfamily D member 3 and is located in a genome-wide significant COPD GWAS region, although the COPD-associated top SNP is located about 575 Kb from the transcription start site. The expression of PRDX4 is strongly positively correlated in the COPD correlation network with SERPINE2, CD79A, and POUF2AF1, which were previously considered as putative interactors of genes at COPD GWAS loci [Morrow 2017]. The expression of KCND3 is strongly positively correlated with two of them (SERPINE2 and CD79A).…”
Section: Summarizing the Profiles Of The Copd Modulesmentioning
confidence: 90%
See 2 more Smart Citations